Accelerating and decelerating flow of radiatively Casson fluid between two permeable disks under convective boundary conditions - A. Naeem; Z. Abbas; M.Y. Rafiq (Case Studies in Thermal Engineering)
The fully developed flow between two flat radial disks has much significance in industrial and technological fields. Therefore, this work deals with the hydromagnetic flow of incompressible Casson fluid between two permeable parallel disks under convective surface constraints. The impacts of thermal radiation and heat generation/absorption are also incorporated into the energy equation. Jacobi elliptic sine square function is used to derive the solution of non-linear differential equations by transforming the equations into an elliptic integral form and then by using a change of variables which simplifies the governing equations so that the solution can be derived easily. Thus, the Jacobi elliptic sine squared function is used to derive the analytical solution of accelerating and decelerating flow. The expression for temperature is also derived analytically. The graphical representations are given to depict the impacts of various significant parameters on velocity, temperature, and Nusselt number while the effect for torque and skin friction is given in tabular form. A parabolic velocity profile with maximum velocity at the center and minimum velocity at the surface of the disks is obtained. Accelerating velocity decreases with the increase in porosity, Casson fluid, and pressure gradient parameter while rising with the increment in magnetic effect while the decelerating velocity declines with the upsurge in all the parameters. The liquid temperature upsurges for the escalation in heat source/sink parameter while diminutions for thermal radiation parameter and Biot number. With the increase in Darcy's number, torque on the lower disk increases while decreasing for the upper disk while the skin friction shows the opposite behavior for both disks.